FACTORS AFFECTING ONLINE PURCHASE DECISION OF GENERATION Z IN SHOPEE APPLICATION - Julitri Ivie Karame; Maryam Mangantar; Emilia Gunawan (Universitas Sam Ratulangi, 2023)
This study aims to analyse the factors that affecting online purchase decisions of Generation Z on the Shopee application in Manado. The Population in this study is Generation Z Shopee users in Manado who have made transaction/purchases. The number of sample in this study were 96 respondents. The sampling method used non-probability sampling technique, namely purposive sampling. The data was processed by multiple linear regression method. The result of this study found that trust, easiness, security, and e-service quality simultaneously have a significant and positive effect on Generation Z online purchase decision in Shopee application. Based on the partial test, trust, easiness, and e-service quality have a positive and significant effect on generation Z online purchase decision, while security has a negative and no significant effect on generation Z online purchase decision. Keywords: trust, easiness, security, e-service quality, and online purchase decision